2001
DOI: 10.1002/jsfa.982
|View full text |Cite
|
Sign up to set email alerts
|

Content of bioactive compounds in pungent spice red pepper (paprika) as affected by ripening and genotype

Abstract: This work was conducted to investigate changes in the bioactive nutrient content of hot (pungent) paprika as a function of ripening in four of the most important varieties cultivated in Hungary. For the quantitative determination, recent liquid chromatographic (HPLC) methods were applied. Forty carotenoids were separated, with b-carotene and lutein of interest from the biological point of view. The major component of vitamin E was a-tocopherol. Capsaicin, dihydrocapsaicin and nordihydrocapsaicin were the domin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
35
2
4

Year Published

2003
2003
2019
2019

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 103 publications
(54 citation statements)
references
References 17 publications
(16 reference statements)
13
35
2
4
Order By: Relevance
“…In addition, the present study confirms that capsaicin is the primary capsaicinoid component in almost all of the analyzed Capsicum genotypes. However, the total capsaicinoids concentration showed intra-specific as well as inter-specific variations as reported earlier [41,42,43,44,45,46]. The present study identified 17 genotypes from C .…”
Section: Discussionsupporting
confidence: 83%
“…In addition, the present study confirms that capsaicin is the primary capsaicinoid component in almost all of the analyzed Capsicum genotypes. However, the total capsaicinoids concentration showed intra-specific as well as inter-specific variations as reported earlier [41,42,43,44,45,46]. The present study identified 17 genotypes from C .…”
Section: Discussionsupporting
confidence: 83%
“…According to Chennupati, Seguin, and Liu (2011), the changes of tocopherols content during soybean development could be attributed to temperature stress and genotype, with different responses between various genotypes. Moreover, Gnayfeed, Daood, Biacs, and Alcaraz (2001) have reported a significant increase of alpha-tocopherol during red pepper ripening, while similar results have been reported by Dhillon et al (2016) and Saini, Zamany, and Keum (2017) for bitter gourd (Momordica charantia L.) and tomato fruit (Solanum lycopersicum L.), respectively Considering, the antioxidant properties of tocopherols, harvesting at early stages of fruit development is essential for pod quality for most of the studied genotypes, whereas especially for cv. "Pylaea" and "Boyati" which are usually harvested at small size, harvesting fruit at larger size should be considered with care and only if market standards are met.…”
Section: Resultssupporting
confidence: 71%
“…Our results agreed with these findings, and 45 DFS contained more ascorbic acid. Furthermore, other authors have found that ascorbic acid increased or remained constant as pepper fruits matured (Howard et al, 2000), and declined with further ripening (Gnayfeed et al, 2001). Our results also supported these findings.…”
Section: Ascorbic Acid Contentsupporting
confidence: 92%